2019
DOI: 10.1016/j.drugalcdep.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity and discriminative stimulus effects of five novel synthetic cathinone analogs in mice and rats

Abstract: Background: The development of novel synthetic psychoactive substances continues to accelerate. There are little or no data on the pharmacological mechanisms, behavioral effects, or abuse liability of many of the newer compounds, despite increasing reports of severe adverse effects in recreational users. Methods: The current study investigated the discriminative stimulus and locomotor stimulant effects of a group of synthetic cathinone analogs: N-ethylpentylone, dimethylone, dibutylone, clephedrone, 3',4'-tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
6
24
1
Order By: Relevance
“…Interestingly, the locomotor stimulation evoked by 4-CMC was less pronounced at 20 mg/kg compared with 10 mg/kg, because of a slower onset, presumably associated with an incidence of stereotypies in some mice during the initial 60 min after treatment (Supplementary Material 1 ). Our results are in line with previously reported locomotor stimulation observed in Swiss-Webster mice (Gatch et al 2019 ) treated with 4-CMC (2.5 and 5 mg/kg), where the similar pattern of locomotor stimulation, with a slow onset and long duration, was observed after treatment with 4-CMC and MDMA. Interestingly, in the current study, the onset of locomotor stimulation induced by 4-CMC at the highest tested dose of 20 mg/kg was also significantly delayed, similarly to MDMA (50 mg/kg) reported by Gatch and coworkers ( 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the locomotor stimulation evoked by 4-CMC was less pronounced at 20 mg/kg compared with 10 mg/kg, because of a slower onset, presumably associated with an incidence of stereotypies in some mice during the initial 60 min after treatment (Supplementary Material 1 ). Our results are in line with previously reported locomotor stimulation observed in Swiss-Webster mice (Gatch et al 2019 ) treated with 4-CMC (2.5 and 5 mg/kg), where the similar pattern of locomotor stimulation, with a slow onset and long duration, was observed after treatment with 4-CMC and MDMA. Interestingly, in the current study, the onset of locomotor stimulation induced by 4-CMC at the highest tested dose of 20 mg/kg was also significantly delayed, similarly to MDMA (50 mg/kg) reported by Gatch and coworkers ( 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previously reported locomotor stimulation observed in Swiss-Webster mice (Gatch et al 2019 ) treated with 4-CMC (2.5 and 5 mg/kg), where the similar pattern of locomotor stimulation, with a slow onset and long duration, was observed after treatment with 4-CMC and MDMA. Interestingly, in the current study, the onset of locomotor stimulation induced by 4-CMC at the highest tested dose of 20 mg/kg was also significantly delayed, similarly to MDMA (50 mg/kg) reported by Gatch and coworkers ( 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…An apparent exception was TH-PVP, which is also a substituted alpha-pyrrolidine, but completely failed to produce MDMA-like effects (Gatch et al, 2019). However, TH-PVP also produced very little cocaine- and methamphetamine-like effects in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, methylone and butylone fully substituted for the discriminative stimulus effects of MDMA in rats, whereas pentylone did not (Dolan et al, 2018). In another study, dimethylone, dibutylone, and clephedrone fully substituted for MDMA, whereas N-ethylpentylone did not (Gatch et al, 2019). More recently, the cathinones 4-fluoromethcathinone, 4-methylmethcathinone, 4-methylethcathinone, 3-fluoromethcathinone, pentedrone, and ethylone fully substituted for the discriminative stimulus effects of ±-MDMA, whereas methcathinone did not (Gatch and Forster, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 3-CMC was inactive at all tested doses, while the increase of vertical activity in mice treated with 4-CMC was significant only at the middle dose of 10 mg/kg. Recently, Gatch et al (2019) demonstrated stimulation of horizontal locomotor activity in Swiss-Webster mice by 4-CMC (1-10 mg/kg). Reported effects were delayed, peaking 30-60 min after administration, and long lasting.…”
Section: Discussionmentioning
confidence: 99%